DIGITAL TECHNOLOGIES IN THE LESSONS RUSSIAN LANGUAGE AND LITERATURE - Khasanova, Alina23 (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
Today, the Internet environment is becoming the most important source of educational information in modern society. Language teachers cannot but take this into account in their daily pedagogical practice. Mastering digital technologies is becoming one of the basic competencies of a teacher.